On-farm evaluation of upland rice genotypes at Bajhang district, mid western hills of Nepal - Ojha, BR (Agronomy Journal of Nepal, 2013)
A set of eight rice (Oryza sativa L.) genotypes in upland condition were evaluated in Bhajhang district. They were compared with popular local and standard check varieties of upland rice with an objective of selecting them to be suited to Bhajhang and similar agro-ecological domains. The genotypes included were; Tauliya, Chhomroung, Kalo Nathre, Rato Ghaiya, Pakhe Jhinuwa, Radha- 32, IR78877-208-B-1-2, and CT- 65110-24-1-1. They were evaluated in a Randomised Complete Block Design (RCBD) with four replication at Rayal VDC-3, Deura, Bajhang, Nepal during 2010 upland paddy growing season. Highly significant variation was observed for traits recorded. Grain yield ranged from 2.1 kg/plot (Radha- 32 and Rato Ghaiya) to 0.52 kg/plot (Pakhe Jhinuwa). Radha- 32 and Rato Ghaiya were found superior to Local checks. Likewise, significant variation was also observed in the morpho-physiological traits such as days to anthesis and days to maturity which varied from 100 days (Tauliya) to 114 days (CT 65110-24-1-1) and 126 days (Tauliya) to 148 days (CT 65110-24-1-1), respectively. Genotype Tauliya was early maturing while CT 65110-24-1-1 was late maturing one. There was a variation in grain filling period which ranged from 24 days (Pakhe Jhinuwa) to 36 days (Chhomroung and IR 78877-208-B-1-2) after anthesis to physiological maturity. Similarly, significant variation was also recorded for plant height, panicle length, and peduncle length. Highly significant positive correlation (r = 0.85, 0.69, 0.54 and 0.83) was found for panicle length, peduncle length, grain filling period and numbers of grains/panicle with grain yield. Likewise, significant positive correlation was found between days to maturity and grain filling duration (0.81), numbers of grains/panicle and panicle length (0.81), 1000 seeds weight, and grain filling duration (0.53). The result of the study revealed that Radha- 32 and Rato Ghaiya were found as the best genotypes so far as farmers and breeders are concerned in the tested site of Bajhang.DOI: http://dx.doi.org/10.3126/ajn.v2i0.7525 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.102-110